2022
DOI: 10.1111/epi.17413
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐resistant epilepsy and mortality—Why and when do neuromodulation and epilepsy surgery reduce overall mortality

Abstract: Patients with drug‐resistant epilepsy have an increased mortality rate, with the majority of deaths being epilepsy related and 40% due to sudden unexpected death in epilepsy (SUDEP). The impact of epilepsy surgery on mortality has been investigated since the 1970s, with increased interest in this field during the past 15 years. We systematically reviewed studies investigating mortality rate in patients undergoing epilepsy surgery or neuromodulation therapies. The quality of available evidence proved heterogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 102 publications
0
6
0
Order By: Relevance
“…A recent meta-analysis demonstrated that patients who underwent epilepsy surgery have a two-fold lower risk of death and a three-fold lower risk of SUDEP, but limited data are available for patients undergoing neuromodulation. 34…”
Section: Non-pharmacological Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis demonstrated that patients who underwent epilepsy surgery have a two-fold lower risk of death and a three-fold lower risk of SUDEP, but limited data are available for patients undergoing neuromodulation. 34…”
Section: Non-pharmacological Treatment Optionsmentioning
confidence: 99%
“…All options have specific advantages and drawbacks with regard to outcome and side effects and are typically used alongside ongoing and optimized ASM regimens. A recent meta‐analysis demonstrated that patients who underwent epilepsy surgery have a two‐fold lower risk of death and a three‐fold lower risk of SUDEP, but limited data are available for patients undergoing neuromodulation 34 …”
Section: Management Of Drug Resistant Epilepsymentioning
confidence: 99%
“…48 Furthermore, neuromodulation through deep brain stimulation has also been associated with decreased SUDEP risk. 49 In addition to reducing seizure frequency, nocturnal supervision may be similarly helpful in modifying SUDEP risk. In epilepsy care centers, the centers with the lowest grade of nocturnal supervision had the highest incidence of SUDEP.…”
Section: Sudep Preventionmentioning
confidence: 99%
“…Vagus nerve stimulation should be considered in patients who are not resective candidates as it may independently reduce the risk of SUDEP, possibly via brainstem mechanisms 48 . Furthermore, neuromodulation through deep brain stimulation has also been associated with decreased SUDEP risk 49 . In addition to reducing seizure frequency, nocturnal supervision may be similarly helpful in modifying SUDEP risk.…”
Section: Sudep Preventionmentioning
confidence: 99%
“…These are resection, ablation, and neuromodulation procedures intended to reduce seizure frequency or severity, but unlikely to cure the epilepsy or result in post‐operative discontinuation of all anti‐seizure medications. However, in many children and adults, surgeries that reduce seizures may provide considerable benefit, improving quality of life and cognitive function, and reducing the risk of sudden death or injury 1–3 . Furthermore, some patients who continue to have seizures after epilepsy surgery may become seizure‐free in a delayed fashion, or have extended periods of several months without seizures, allowing discontinuation of some concomitant treatments while limiting polypharmacy and the associated adverse effects 4 .…”
mentioning
confidence: 99%